PENELUSURAN MINAT-BAKAT UNTUK SISWA SMA DI YOGYAKARTA - Rostiana, Rostiana; Saraswati, Kiky Dwi Hapsari (Jurnal Bakti Masyarakat Indonesia, 2019)
High school students who have graduated will usually continue to university at their desired major. Unfortunately, there are still schools and parents who do not fully know the correlation between the suitability between students' interests and talents and the success of their studies. As a result of this lack of knowledge, students often fail to receive the right guidance when choosing majors in college. In addition to being successful in their studies and not encounterin problems stemming from choosing the incorrect major, knowing students’ interests and talents can help students to choose the career path that they will pursue after graduation. Interest is the interaction between desires, hopes, experiences or needs that move a person to prefer certain things, while talent is a personal characteristic that directs someone to achieve success (Reed & Wolniak, 2005). In this Community Service activity, the author conducted a Psychology test to acquire an overview of interests and talents in BOPKRI 1, Yogyakarta, 11th grade high school students. The activity carried out in the school environment was attended by 269 students who majored in Mathematics and Natural Sciences, Social Sciences, and Language and Culture. The output of this activity is a description of the intelligence, interests, talents, and recommendations of majors that can be chosen. These results can be used by students, parents, and schools as a reference to determine the college majors suitable for students. ABSTRAK: Siswa SMA yang telah lulus biasanya akan melanjutkan ke perguruan tinggi dengan jurusan yang diinginkannya. Sayangnya, masih ada saja sekolah maupun orang tua yang belum sepenuhnya mengetahui korelasi antara kesesuaian antara minat dan bakat siswa dengan keberhasilan studi. Akibat dari kurangnya pengetahuan ini, siswa seringkali tidak mendapatkan arahan yang tepat ketika ingin menentukan jurusan di bangku kuliah. Selain agar berhasil dalam studinya dan tidak mengalami masalah karena salah mengambil jurusan, lebih jauh lagi, dengan mengetahui minat dan bakat dapat membantu siswa untuk memilih jalur karir yang akan ditekuninya nanti setelah lulus. Minat adalah interaksi antara keinginan, harapan, pengalaman atau kebutuhan yang menggerakan seseorang untuk menyukai hal tertentu, sedangkan bakat adalah karakteristik pribadi yang mengarahkan seseorang untuk meraih kesuksesan (Reed & Wolniak, 2005). Pada kegiatan Pengabdian Masyarakat ini, Penulis melaksanakan Tes Psikologi untuk mendapatkan gambaran minat dan bakat pada siswa kelas XI SMA BOPKRI 1, Yogyakarta. Kegiatan yang dilaksanakan di lingkungan sekolah ini diikuti oleh 269 orang siswa yang mengambil jurusan MIPA, IPS, serta Bahasa dan Budaya. Luaran dari kegiatan ini berupa gambaran tentang kecerdasan, minat, bakat, dan rekomendasi jurusan yang dapat dipilih. Hasil tersebut dapat digunakan oleh siswa, orang tua, dan pihak sekolah sebagai referensi untuk menentukan jurusan yang akan diambil ketika siswa kuliah nantinya.